2011
DOI: 10.1016/j.antiviral.2011.06.005
|View full text |Cite
|
Sign up to set email alerts
|

In vitro inhibition of CSFV replication by multiple siRNA expression

Abstract: Classical swine fever (CSF) is a highly contagious viral disease of pigs which causes major economic losses worldwide. No specific drug is currently available for the effective treatment of CSFV infection; however, RNA interference (RNAi) has been applied successfully to inhibit the replication of human and other animal viruses. In this study, three effective siRNAs targeting NS3 of CSFV were selected. siNS3-2 targeting NS3 gene was chosen for further experimentation, while siN1 and siN2 targeting N(pro) gene,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…The reduction in RV titer in the infected cell culture supernatant was 87.4 %, which was significantly similar to the effect produced by individual siRNAs, indicating no cumulative effect. The approach of using multigene siRNAs or multi-siRNAs/miRNAs targeting a single gene has been reported for many viruses, with a variable degree of inhibition of virus replication [11,[33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…The reduction in RV titer in the infected cell culture supernatant was 87.4 %, which was significantly similar to the effect produced by individual siRNAs, indicating no cumulative effect. The approach of using multigene siRNAs or multi-siRNAs/miRNAs targeting a single gene has been reported for many viruses, with a variable degree of inhibition of virus replication [11,[33][34][35].…”
Section: Discussionmentioning
confidence: 99%
“…Ampicillin-resistant colonies were cultured on solid luria broth medium at 37 C overnight on a rocking bed, and the sequence of the inserted 76 bp siRNA was verified by electrophoresis of the recombinant semaphorin 6B siRNA plasmid. 19 Next, SGC-7901 cells were seeded in sixwell plates (1 Â 10 5 /well in 100 ml) and transfected with 100 nM pSilencer TM plasmid, containing either semaphorin 6B siRNA or control siRNA when confluence reached 90%. Transfection was performed using XtremeGene siRNA transfection reagent (Roche, Indianapolis, IN, USA), according to the manufacturer's instructions.…”
Section: Construction Of Sirna Plasmid Expression Vectormentioning
confidence: 99%
“…(2) Given the transfection efficiency, one vector more effectively expresses multiple shRNAs than can be achieved by cotransfection with multiple shRNAs vectors. (3) Multiple shRNAs can prevent viral escape because that would require acquisition of mutations in all shRNA-target sites [21,22,28] . (4) Previous studies involving the expression of multiple shRNAs employing an expression strategy in which three or four shRNAs were expressed from the same promoters found that this caused frequent recombination at repeat sequences of the expression cassette, resulting in deletion of one or two of the cassettes [2] .…”
Section: Discussionmentioning
confidence: 99%